LABTUR - Laboratorios experimentales para la co-creación del espacio urbano: hacia una metodología de intervención - Cardoso, A. (IV Congreso ISUF-H FORMA URBIS y territorios metropolitanos Metrópolis en recomposición. Prospectivas proyectuales en el siglo XX, 2020)
The city has been the scene of debate in recent decades, as a result of the growing urbanization and the consequent complexity of urban problems, which have imposed profound changes in the way in which the urban space is designed, produced and managed. Experimental co-creation laboratories have been tested as multi-actor reflective learning environments, which promote collective intelligence based on experimentation within a real-world context. Based on the idea of ​​an experimental urban laboratory, the ongoing investigation aims to present the experience of the TUR laboratory developed in the Technopolitics in Urban Regeneration: Co-creating Public Spaces program - a research-action project carried out in an academic environment in partnership with the municipality of Cascais in Portugal. The article presents results from LABTUR - Experimental laboratory for the co-creation of urban space and discusses the learning based on co-creation dynamics, contributing to the definition of an intervention methodology that promotes a more sustainable and inclusive local-based planning.